Laminate and packaging bag
Patent Information
- Application Number
- JP2023129895
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
【0008】 本開示によれば、クリーン環境内で使用される物品を包装できる包装材料として好適で、環境負荷の低い積層体を提供できる。
Smart Images

Figure 2025025271000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate and a packaging bag. [Background technology]
[0002] Semiconductor products are manufactured or used in clean environments such as clean rooms with high levels of cleanliness, because the quality of the products can be reduced if foreign matter such as dust and dirt adheres to the products. When an article is brought into such an environment, a package in which the article is contained in a bag made of plastic film is often brought into the clean environment. Therefore, high cleanliness is also required for packaging bags that contain articles that require a high level of cleanliness, such as semiconductor products.
[0003] Conventionally, a package is manufactured as follows using a double bag having at least an inner bag and an outer bag (see, for example, Patent Document 1). First, an item is placed inside the inner bag, which is vacuum degassed, and the opening of the inner bag is sealed. Next, the inner bag is placed inside the outer bag, which is vacuum degassed, and the opening of the outer bag is sealed. The item is packaged in this double packaging, or triple packaging as necessary. When the item is to be used, the outer bag is opened in the antechamber of the clean room, the clean inner bag is opened inside the clean room, and the item is removed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-126437 A Summary of the Invention [Problem to be solved by the invention]
[0005] When packaging an article using double or triple vacuum packaging, the vacuum packaging is performed multiple times. This may result in low work efficiency in packaging the article. Furthermore, when opening the packaging bag, the multiple openings may be troublesome. Furthermore, in recent years, attention has been focused on addressing environmental issues. From the perspective of addressing environmental issues, there is a demand for packaging bags that have a low environmental impact.
[0006] An object of the present disclosure is to provide a laminate that is suitable as a packaging material capable of packaging articles used in clean environments and that has a low environmental impact. [Means for solving the problem]
[0007] The present inventors have investigated the production of a packaging bag using a laminate having a peelable surface film. By peeling off the surface film of the packaging bag in the antechamber of the clean room, the packaging bag in a clean state can be brought into the clean room. Based on this knowledge, the present inventors have found that the above-mentioned problem can be solved by a laminate having the following configuration. A laminate according to one embodiment of the present disclosure comprises at least a first resin layer and a second resin layer, the first resin layer being provided so as to be peelable from the second resin layer, the second resin layer being a sealant layer containing polyolefin as a main component, and at least one resin layer selected from the first resin layer and the second resin layer containing at least a biomass-derived resin material. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide a laminate that is suitable as a packaging material capable of packaging items used in a clean environment and has a low environmental impact. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Diagram 5] FIG. 5 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. [Figure 6] FIG. 6 is a schematic cross-sectional view of one embodiment of the packaging bag of the present disclosure. [Figure 7] FIG. 7 is a front view of one embodiment of the packaging bag of the present disclosure. [Figure 8] FIG. 8 is a schematic diagram illustrating the half-cut line. [Figure 9] FIG. 9 is a front view illustrating the production of a packaging bag. [Figure 10] FIG. 10 is a schematic cross-sectional view of one embodiment of a laminate of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present disclosure will be described in detail. The present disclosure can be implemented in many different forms, and is not to be interpreted as being limited to the description of the embodiments exemplified below. In the drawings, the width, thickness, shape, etc. of each layer may be shown diagrammatically in order to make the explanation clearer, but these are merely examples and do not limit the interpretation of the present disclosure. In this specification and each figure, elements similar to those already explained with respect to the previous figures are given the same reference numerals, and detailed explanations may be omitted as appropriate.
[0011] In the present disclosure, when multiple upper limit candidates and multiple lower limit candidates are listed for a certain parameter, the numerical range of the parameter may be configured by combining any one upper limit candidate and any one lower limit candidate. Examples of the above parameters include physical property values, component content ratios, and layer thicknesses. As an example, the description "Parameter B is preferably A1 or more, more preferably A2 or more, and even more preferably A3 or more. Parameter B is preferably A4 or less, more preferably A5 or less, and even more preferably A6 or less." will be explained. In this example, the numerical range of parameter B may be A1 or more and A4 or less, A1 or more and A5 or less, A1 or more and A6 or less, A2 or more and A4 or less, A2 or more and A5 or less, A2 or more and A6 or less, A3 or more and A4 or less, A3 or more and A5 or less, or A3 or more and A6 or less.
[0012] In the following description of this specification, each of the components (e.g., polyolefins such as polyethylene and polypropylene, α-olefins, resin materials such as heteroatom-containing resins, and additives) that appear may be used alone or in combination of two or more kinds.
[0013] In this specification, polyethylene refers to a polymer in which the content of ethylene-derived structural units in all repeating structural units exceeds 50 mol%. In this polymer, the content of ethylene-derived structural units is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 95 mol% or more. The content is measured by NMR.
[0014] In this specification, polyethylene may be a homopolymer of ethylene, or a copolymer of ethylene and an ethylenically unsaturated monomer other than ethylene. Examples of the ethylenically unsaturated monomer other than ethylene include α-olefins having 3 to 20 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene, vinyl monomers such as vinyl acetate and vinyl propionate, and (meth)acrylic acid esters such as methyl (meth)acrylate and ethyl (meth)acrylate.
[0015] In this specification, polyethylene includes, for example, high density polyethylene, medium density polyethylene, low density polyethylene and linear low density polyethylene, as well as ethylene-vinyl acetate copolymer and ethylene-(meth)acrylic acid ester copolymer.
[0016] In this specification, the density of polyethylene is as follows: The density of the high density polyethylene is preferably 0.945 g / cm 3 The density of the high density polyethylene is preferably greater than 0.965 g / cm 3 The density of the medium density polyethylene is preferably 0.932 g / cm 3 Exceeds 0.945g / cm 3 The density of the low density polyethylene is preferably 0.860 g / cm 3 More than 0.932g / cm 3 Less than or equal to 0.900 g / cm 3 More than 0.932g / cm 3 The density of the linear low density polyethylene is preferably 0.860 g / cm 3 More than 0.932g / cm 3 Less than or equal to 0.900 g / cm 3 More than 0.932g / cm 3The density of polyethylene is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23°C).
[0017] Low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene by high-pressure polymerization (high-pressure low-density polyethylene). Linear low-density polyethylene is, for example, polyethylene obtained by polymerizing ethylene and a small amount of α-olefins by a polymerization method using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst.
[0018] Polyethylenes with different densities or branches can be obtained by appropriately selecting a polymerization method. For example, it is preferable to carry out polymerization in one or more stages by using a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst as a polymerization catalyst, by any of gas phase polymerization, slurry polymerization, solution polymerization, and high pressure ion polymerization.
[0019] The polyethylene may be mechanically recycled or chemically recycled. This can reduce the environmental impact of laminates or packaging bags. Mechanical recycling is generally a method in which recovered polyethylene films are crushed, washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse contaminants remaining inside the film, decontaminating it, removing the dirt from the film, and returning it to polyethylene. Chemical recycling is generally a method in which recovered polyethylene films are decomposed to the monomer level, and the monomers are polymerized again to obtain polyethylene.
[0020] In this specification, the "main component" of a certain layer refers to a component whose content in the layer is more than 50% by mass, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0021] [Laminate] The laminate of the present disclosure includes at least a first resin layer and a second resin layer. The second resin layer has a first surface and a second surface opposite to the first surface. The first resin layer is provided on the first surface of the second resin layer. The first resin layer is in contact with the second resin layer, specifically, in contact with the first surface of the second resin layer. Therefore, the first surface of the second resin layer is usually a peeling surface when peeling off the first resin layer.
[0022] At least one resin layer selected from the first resin layer and the second resin layer contains a biomass-derived resin material (hereinafter also referred to as "biomass material"). The biomass material is, for example, a resin material obtained by using a biomass-derived raw material (specifically, a plant-derived raw material) as at least a part of the raw material. Since the biomass material is a carbon-neutral material, it can reduce the environmental load caused by the laminate or the packaging bag.
[0023] Examples of biomass materials include polyolefins such as polyethylene synthesized using ethylene obtained from biomass-derived ethanol (fermented ethanol) obtained from plant raw materials as at least a part of the raw material monomer, and polypropylene synthesized using propylene obtained from waste edible oils and the like as at least a part of the raw material monomer, polyesters synthesized using biomass-derived diol components and / or biomass-derived dicarboxylic acid components as at least a part of the raw material monomer, and polyamides synthesized using biomass-derived dicarboxylic acids and / or biomass-derived diamines as at least a part of the raw material monomer. Hereinafter, each biomass material will also be referred to as biomass polyolefins such as biomass polyethylene and biomass polypropylene, biomass polyesters, and biomass polyamides. Examples of plant raw materials include corn, sugarcane, beets, and manioc. The plant raw materials may also be plant-derived oils such as soybean oil, linseed oil, tung oil, coconut oil, palm oil, and castor oil, as well as regenerated oils obtained by recycling waste edible oils mainly composed of these.
[0024] The biomass material may be a resin material composed of 100% by mass of raw material monomers derived from biomass, or may be a resin material composed of raw material monomers derived from fossil fuels together with raw material monomers derived from biomass. In other words, the biomass content of the biomass material described below does not have to be 100%.
[0025] In this specification, the term "biomass degree" (also referred to as biobased carbon content) refers to the percentage of pMC (percent modern carbon) measured in accordance with Method B of ASTM D6866-22, expressed as δ 13 This value is obtained by correcting for the carbon dioxide (CO2) in the sample. Specifically, the sample is burned to generate carbon dioxide (CO2), which is then purified in a vacuum line. The purified carbon dioxide is reduced with hydrogen using iron as a catalyst to generate graphite. The resulting graphite is then analyzed by accelerator mass spectrometry (AMS). 14 C counts and carbon isotope ratios ( 14 C / 12 C. 13 C / 12 C) is measured. 14 A dedicated C-AMS device (manufactured by NEC) can be used. Oxalic acid (HOxII) provided by the National Institute of Standards (NIST) is used as the standard sample. Measurements of this standard sample and a background sample are also performed simultaneously. From the obtained carbon isotope ratio, the sample's relative carbon isotope ratio to the standard sample can be calculated. 14 C / 12 Calculate the relative ratio (pMC) of C. 13 C is the carbon of the sample 13 C / 12 C is measured and the deviation from a standard sample is expressed in thousandths.
[0026] Bio-based carbon content is the carbon dioxide released into the atmosphere due to nuclear testing. 14 Since C is in excess, the value is obtained by multiplying pMC by a correction factor. 14Due to the continuous decrease in C, the correction factor shall be in accordance with ASTM D6866-22.
[0027] Fossil fuel-derived materials contain radioactive carbon with mass number 14 ( 14 C), whereas plant-derived materials do not contain 14 Since it contains C, 14 The two can be distinguished by the biomass ratio, which is based on the C content. As such, materials derived from fossil fuels are known to have a biomass ratio of approximately 0%. The biomass ratio is an index that represents the mixture ratio of fossil fuel-derived materials and plant-derived materials.
[0028] When measuring the biomass degree of the entire laminate, a sample may be prepared from the laminate. When measuring the biomass degree of each layer in the laminate, a target layer may be separated from the laminate and a sample may be prepared.
[0029] Examples of biomass polyethylene include biomass high density polyethylene, biomass medium density polyethylene, biomass low density polyethylene, and biomass linear low density polyethylene. Examples of biomass polyester include biomass polyethylene terephthalate.
[0030] Examples of biomass polyamides include polyamide 56 (PA56), polyamide 410 (PA410), polyamide 510 (PA510), polyamide 610 (PA610), polyamide 810 (PA810), polyamide 910 (PA910), polyamide 1010 (PA1010), polyamide 1012 (PA1012), polyamide 11 (PA11) and polyamide 12 (PA12). Polyamide 410 is obtained, for example, from tetramethylenediamine and sebacic acid. Polyamide 610 is obtained, for example, from hexamethylenediamine and sebacic acid. Polyamide 11 is obtained, for example, by condensation polymerization of 11-aminoundecanoic acid. Polyamide 1010 is obtained, for example, from sebacic acid and 1,10-decanediamine obtained by amminating sebacic acid. Sebacic acid can be obtained from castor oil. 11-aminoundecanoic acid can be obtained from castor oil. Polyamide 11 and polyamide 1010 are preferred due to their high biomass content.
[0031] The biomass degree of the biomass material is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, still more preferably 80% or more, particularly preferably 85% or more, 90% or more, or 95% or more.
[0032] The biomass degree of the laminate of the present disclosure is preferably 1% or more, more preferably 3% or more, even more preferably 5% or more, still more preferably 10% or more, particularly preferably 15% or more, and may be 60% or less, 50% or less, 40% or less, 35% or less, or 30% or less, for example, 1% or more and 60% or less. Such a laminate or a packaging bag including the laminate can reduce the environmental load.
[0033] <First resin layer> The first resin layer is provided so as to be peelable from the second resin layer. In this specification, the film consisting of the first resin layer obtained by peeling the first resin layer from the second resin layer of the laminate of the present disclosure is also called a "peeling film." The film consisting of the second resin layer after the peeling is also called a "sealant film."
[0034] The peel strength between the first resin layer and the second resin layer is preferably 1.0 N / 15 mm width or less, more preferably 0.9 N / 15 mm width or less, even more preferably 0.8 N / 15 mm width or less, even more preferably 0.7 N / 15 mm width or less, and particularly preferably 0.6 N / 15 mm width or less. In the case of a laminate having such a peel strength, the first resin layer can be easily peeled from the second resin layer with a moderate force without damaging the second resin layer. The above peel strength is, for example, 0.01 N / 15 mm width, 0.05 N / 15 mm width, or 0.1 N / 15 mm width or more, preferably 0.15 N / 15 mm width or more, more preferably 0.2 N / 15 mm width or more. In the case of a laminate having such a peel strength, the lifting of the first resin layer from the second resin layer can be suppressed, the appearance of the laminate is excellent, and the first resin layer can be suppressed from being peeled off from the second resin layer at an unintended time.
[0035] The peel strength is measured under the conditions of a peel angle of 180 degrees and a test speed of 50 mm / min. Specifically, the laminate is cut to cut out a test piece having a size of 15 mm in width and 100 mm in length. The first resin layer at one end in the length direction of the test piece is peeled off and folded back, and the end of the partially peeled first resin layer (peeling film) is attached to one grip of a tensile tester, and the end of the partially peeled second resin layer (sealant film) is attached to the other grip of the tensile tester. The initial chuck distance is 100 mm. Next, the grip to which the end of the first resin layer is attached is pulled at a speed of 50 mm / min in a direction of 180 degrees with respect to the surface of the test piece while maintaining the position of the test piece so that the angle is maintained, and the maximum strength (N) is measured. The maximum strength (N) measured for the 15 mm wide test piece is taken as the peel strength (N / 15 mm width).
[0036] From the viewpoints of peelability, strength, and heat resistance, the thickness of the first resin layer is preferably 3 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, and particularly preferably 15 μm or more. From the viewpoint of processability, the thickness of the first resin layer is preferably 150 μm or less, more preferably 130 μm or less, even more preferably 100 μm or less, and particularly preferably 50 μm or less.
[0037] The content ratio of the same resin material having the largest content in the first resin layer is preferably 70% by mass or more, more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 85% by mass or more, and particularly preferably 90% by mass or more, based on the mass of the first resin layer. A laminate having such a first resin layer has excellent recyclability. Specifically, the release film obtained by peeling the first resin layer from the laminate has excellent recyclability.
[0038] In this specification, the same type of resin material refers to, for example, polymers classified as polyolefin resins, polymers classified as polyamides, polymers classified as ethylene-vinyl alcohol copolymers, and polymers classified as polyesters. For example, polyolefin resins and polyesters are not classified as the same type of resin material.
[0039] In one embodiment, the above-mentioned "content ratio of the same type of resin material in the first resin layer" can be read as "content ratio of polyamide in the first resin layer," "content ratio of ethylene-vinyl alcohol copolymer in the first resin layer," "content ratio of polyester in the first resin layer," or "content ratio of polyethylene-based resin in the first resin layer."
[0040] In this specification, the term "polyolefin-based resin" refers to a concept that includes not only polyolefins but also modified polyolefins such as acid-modified polyolefins. In this specification, the term "polyethylene-based resin" refers to a concept that includes not only polyethylene but also modified polyethylenes such as acid-modified polyethylene.
[0041] In one embodiment, the first resin layer may include a heteroatom-containing resin layer containing a heteroatom-containing resin as a main component. The first resin layer may be a heteroatom-containing resin layer, or may include a heteroatom-containing resin layer and a polyolefin layer containing a polyolefin as a main component. In one embodiment, the heteroatom-containing resin layer may be in contact with the second resin layer. The laminate of this embodiment has excellent peelability of the first resin layer from the second resin layer. In one embodiment, the heteroatom-containing resin layer in the first resin layer has a density of 0.909 g / cm 3 It is in contact with the following polyethylene layer. The laminate of such an embodiment has an excellent balance between the peelability of the first resin layer from the second resin layer and the adhesion between the first resin layer and the second resin layer.
[0042] The laminate of the present disclosure has a density of 0.909 g / cm in the polyolefin layer and the second resin layer in the first resin layer. 3 A heteroatom-containing resin layer may be provided between the following polyethylene layer. The laminate of the present disclosure may include a polyolefin layer as a surface layer. Such a laminate has excellent appearance, and the heteroatom-containing resin layer can be made thin, thereby reducing production costs.
[0043] In one embodiment, the first resin layer may include a heteroatom-containing resin layer, an adhesive layer, and a heteroatom-containing resin layer in this order in the thickness direction.
[0044] In one embodiment, the first resin layer may be a polymethylpentene layer containing polymethylpentene as a main component.
[0045] In one embodiment, the biomass degree of the first resin layer is preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, still more preferably 40% or more, and particularly preferably 50% or more, and may be 99% or less, 90% or less, 80% or less, or 70% or less. Such a laminate or a packaging bag including the laminate can reduce the environmental load.
[0046] (Heteroatom-containing resin layer) The heteroatom-containing resin layer contains a heteroatom-containing resin as a main component. The first resin layer including the heteroatom-containing resin layer has a high Young's modulus and is excellent in peelability from the second resin layer. In addition, the laminate including the heteroatom-containing resin layer is excellent in puncture resistance. Therefore, a packaging bag including such a laminate is excellent in packaging hard items. The laminate including the heteroatom-containing resin layer is excellent in gas barrier properties such as oxygen barrier properties and water vapor barrier properties, heat resistance, and rigidity. The heteroatom-containing resin may be a biomass material from the viewpoint of reducing environmental load.
[0047] Examples of the heteroatom in the heteroatom-containing resin include oxygen, sulfur, nitrogen, and chlorine atoms. The heteroatom-containing resin has a heteroatom-containing group such as a hydroxy group, an amide bond, an ester bond, and an ether bond. Examples of the heteroatom-containing resin include polyamide, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, polyvinylidene chloride, polyester, polyether polyol, and polyester polyol. Among these, polyamide, ethylene-vinyl alcohol copolymer, polyester, and polyvinyl alcohol are preferred from the viewpoints of heat resistance, rigidity, and puncture resistance, and polyamide and ethylene-vinyl alcohol copolymer are more preferred. These resin materials may be biomass materials from the viewpoint of reducing environmental load.
[0048] Examples of the polyamide include aliphatic polyamides and semi-aromatic polyamides. As the polyamide, aliphatic polyamides are preferred, and crystalline aliphatic polyamides are more preferred.
[0049] Examples of the aliphatic polyamide include aliphatic homopolyamide and aliphatic copolymer polyamide. In the following examples, polyamide is also referred to as "PA."
[0050] Specific examples of aliphatic homopolyamides include polycaprolactam or poly(6-aminocaproic acid) (PA6), polyenantholactam or poly(7-aminoenanthic acid) (PA7), polyundecane lactam or poly(11-aminoundecanoic acid) (PA11), polylauryllactam or poly(12-aminolauric acid) (PA12), polypentamethylene adipamide (PA56), polyhexamethylene adipamide (PA66), polytetramethylene sebacamide (PA410), polytetramethylene dodecamide (PA412), polypentamethylene azelamide (PA59), polypentamethylene sebacamide (PA510), polypentamethylene dodecamide (PA512), polyhexamethylene azelamide (PA69), Polyhexamethylene sebacamide (PA610), polyoctamethylene sebacamide (PA810), polyhexamethylene dodecamide (PA612), polynonamethylene adipamide (PA96), polynonamethylene azelamide (PA99), polynonamethylene sebacamide (PA910), polynonamethylene dodecamide (PA912), polydecamethylene adipamide (PA1 06), polydecamethylene azelamide (PA109), polydecamethylene decamamide (PA1010), polydecamethylene dodecamide (PA1012), polydodecamethylene adipamide (PA126), polydodecamethylene azelamide (PA129), polydodecamethylene sebacamide (PA1210) and polydodecamethylene dodecamide (PA1212).
[0051] Specific examples of aliphatic copolymer polyamides include caprolactam / hexamethylenediaminoadipic acid copolymer (PA6 / 66), caprolactam / hexamethylenediaminoazelaic acid copolymer (PA6 / 69), caprolactam / hexamethylenediaminosebacic acid copolymer (PA6 / 610), caprolactam / hexamethylenediaminoundecanoic acid copolymer (PA6 / 611), caprolactam / hexamethylenediaminododecanoic acid copolymer (PA6 / 612), caprolactam / amino undecanoic acid copolymer (PA6 / 11), caprolactam / lauryllactam copolymer (PA6 / 12), caprolactam / hexamethylenediaminoadipic acid / lauryllactam copolymer (PA6 / 66 / 12), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminosebacic acid copolymer (PA6 / 66 / 610), caprolactam / hexamethylenediaminoadipic acid / hexamethylenediaminododecanedicarboxylic acid copolymer (PA6 / 66 / 612).
[0052] The relative viscosity of the aliphatic polyamide is preferably 1.5 or more, more preferably 2.0 or more, and even more preferably 2.5 or more. The relative viscosity of the aliphatic polyamide is preferably 5.0 or less, more preferably 4.5 or less. The relative viscosity of the aliphatic polyamide is measured at 25°C by dissolving 1g of polyamide in 100mL of 96% concentrated sulfuric acid in accordance with JIS K6920-2:2009.
[0053] The semi-aromatic polyamide is a polyamide having a constitutional unit derived from an aromatic diamine and a constitutional unit derived from an aliphatic dicarboxylic acid, or a polyamide having a constitutional unit derived from an aliphatic diamine and a constitutional unit derived from an aromatic dicarboxylic acid, for example, a polyamide composed of an aromatic diamine and an aliphatic dicarboxylic acid, or a polyamide composed of an aliphatic diamine and an aromatic dicarboxylic acid.
[0054] Examples of semi-aromatic polyamides include polyhexamethylene terephthalamide (PA6T), polyhexamethylene isophthalamide (PA6I), polynonamethylene terephthalamide (PA9T), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (PA66 / 6T), polyhexamethylene adipamide / polyhexamethylene isophthalamide copolymer (PA66 / 6I), polyhexamethylene terephthalamide / polycaproamide copolymer (PA6T / 6), polyhexamethylene isophthalamide / polycaproamide copolymer (PA6I / 6), polyhexamethylene terephthalamide / poly dodecamide copolymer (PA6T / 12), polyhexamethylene isophthalamide / polyhexamethylene terephthalamide copolymer (PA6I / 6T), polyhexamethylene terephthalamide / poly(2-methylpentamethylene terephthalamide) copolymer (PA6T / M5T), polyhexamethylene adipamide / polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (PA66 / 6T / 6I), polyhexamethylene adipamide / polycaproamide / polyhexamethylene isophthalamide copolymer (PA66 / 6 / 6I) and polymetaxylylene adipamide (PAMXD6).
[0055] The melt volume rate (MVR) of the semi-aromatic polyamide is preferably 5 cm 3 / 10 minutes or more, preferably 10cm 3 The MVR of the semi-aromatic polyamide is preferably 200 cm 3 / 10 minutes or less, preferably 100cm 3 / 10 minutes or less. MVR is measured at a temperature of 275°C and a load of 5.00 kg in accordance with JIS K7210-1:2014.
[0056] The polyamide is preferably a crystalline aliphatic polyamide, such as PA6, PA11, PA12, PA66, PA610, PA612, PA1010, PA6 / 66, and PA6 / 66 / 12.
[0057] The melting point (Tm) of the crystalline aliphatic polyamide is preferably 170° C. or higher, more preferably 180° C. or higher. The Tm of the crystalline aliphatic polyamide is preferably 300° C. or lower, more preferably 250° C. or lower, and even more preferably 230° C. or lower. The Tm of the crystalline aliphatic polyamide is the melting peak temperature obtained by differential scanning calorimetry (DSC) in accordance with JIS K7121:2012.
[0058] From the viewpoint of film-forming property and processability, the polyamide melt flow rate (MFR) is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the polyamide MFR is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The polyamide MFR is measured by the A method at a temperature of 235°C and a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature can be changed depending on the melting point of the polyamide.
[0059] From the viewpoint of reducing the environmental load, biomass polyamides may be used as the polyamides. Examples of biomass polyamides include PA56, PA410, PA510, PA610, PA810, PA910, PA1010, PA1012, PA11, and PA12.
[0060] Ethylene-vinyl alcohol copolymer (EVOH) can be obtained, for example, by copolymerizing ethylene with a vinyl ester monomer and then saponifying the copolymer. The copolymerization of ethylene with a vinyl ester monomer can be carried out by any known polymerization method, such as solution polymerization, suspension polymerization, or emulsion polymerization.
[0061] As the vinyl ester monomer, vinyl acetate is generally used, but other vinyl ester monomers may be used, such as aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate.
[0062] The content of structural units derived from ethylene in EVOH (ethylene content) is preferably 20 mol% or more, more preferably 25 mol% or more, from the viewpoint of processability of the laminate. The ethylene content in EVOH is preferably 60 mol% or less, more preferably 50 mol% or less, from the viewpoint of heat resistance, oxygen barrier property, and water vapor barrier property of the laminate. The ethylene content is measured by NMR.
[0063] The average saponification degree of EVOH is preferably 90 mol% or more, more preferably 95 mol% or more, and further preferably 99 mol% or more. The average saponification degree is measured in accordance with JIS K6726:1994 (wherein EVOH is used as a solution uniformly dissolved in a water / methanol solvent).
[0064] From the viewpoint of heat resistance, the melting point (Tm) of EVOH is preferably 140° C. or higher, more preferably 145° C. or higher, and even more preferably 150° C. or higher. The Tm of EVOH is preferably 200° C. or lower, more preferably 195° C. or lower, and even more preferably 190° C. or lower. The Tm of EVOH is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0065] From the viewpoint of film-forming property and processability, the melt flow rate (MFR) of EVOH is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the MFR of EVOH is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of EVOH is measured by the A method at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature may be 210° C. depending on the melting point of EVOH.
[0066] EVOH may be modified by a known method, such as urethanization, acetalization, cyanoethylation, or oxyalkylenation.
[0067] The average saponification degree of polyvinyl alcohol (PVA) is preferably 70 mol% or more, more preferably 75 mol% or more, further preferably 80 mol% or more, and particularly preferably 85 mol% or more. The average saponification degree is measured in accordance with JIS K6726:1994.
[0068] Examples of polyesters include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), 1,4-polycyclohexylene dimethylene terephthalate, and terephthalic acid-cyclohexanedimethanol-ethylene glycol copolymer. Among these, PET is preferred.
[0069] The content of the heteroatom-containing resin in the heteroatom-containing resin layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more, which can improve the above-mentioned physical properties such as the heat resistance of the packaging bag.
[0070] The heteroatom-containing resin layer may contain additives, such as antiblocking agents, slip agents, UV absorbers, antioxidants, light stabilizers, fillers, reinforcing agents, antistatic agents, compatibilizers, crosslinking agents, pigments, and dyes.
[0071] From the viewpoint of heat resistance of the laminate, the thickness of the heteroatom-containing resin layer is preferably 0.5 μm or more, more preferably 1 μm or more, even more preferably 3 μm or more, and particularly preferably 5 μm or more. From the viewpoint of recyclability of the laminate, the thickness of the heteroatom-containing resin layer is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less.
[0072] (Polyolefin layer) The polyolefin layer in the first resin layer contains polyolefin as a main component. Examples of polyolefin include polyethylene, polypropylene, and polymethylpentene. The polyolefin layer is preferably a polyethylene layer or a polypropylene layer, and more preferably a polyethylene layer. The polyolefin may be a biomass polyolefin from the viewpoint of reducing the environmental load.
[0073] From the viewpoint of film-forming property and processability, the MFR of the polyolefin is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the MFR of the polyolefin is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of the polyolefin is measured by the A method under a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature of the MFR is set according to the melting point of the polyolefin, and is 190 ° C. for polyethylene and 230 ° C. for polypropylene.
[0074] The content of polyolefin in the polyolefin layer is preferably more than 50% by mass, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more.
[0075] The polyolefin layer in the first resin layer may further contain a modified polyolefin from the viewpoint of adhesion to the heteroatom-containing resin layer. The modified polyolefin may be, for example, a polyolefin modified with an unsaturated carboxylic acid such as maleic acid or fumaric acid, or an acid anhydride, ester, or metal salt thereof, particularly a graft modified polyolefin. The modified polyolefin may be a biomass material from the viewpoint of reducing the environmental load.
[0076] From the viewpoint of film-forming property and processability, the MFR of the modified polyolefin is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the MFR of the modified polyolefin is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of the modified polyolefin is measured by the A method under a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature of the MFR is set according to the melting point of the modified polyolefin, and is 190 ° C. for modified polyethylene and 230 ° C. for modified polypropylene.
[0077] The content of the modified polyolefin in the polyolefin layer is preferably less than 50% by mass, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less. The content of the modified polyolefin in the polyolefin layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more.
[0078] The polyolefin layer may contain a resin material other than polyolefin and modified polyolefin, such as (meth)acrylic resin, vinyl resin, cellulose resin, polyamide, polyester, and ionomer resin.
[0079] The polyolefin layer may contain the additives described above.
[0080] The thickness of the polyolefin layer is preferably 1 μm or more, more preferably 5 μm or more, and even more preferably 10 μm or more from the viewpoint of the strength, heat resistance, and recyclability of the laminate. The thickness of the polyolefin layer is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less from the viewpoint of the processability of the laminate.
[0081] ((Polyethylene layer)) The polyethylene layer in the first resin layer contains polyethylene as a main component. Examples of polyethylene include high-density polyethylene, medium-density polyethylene, low-density polyethylene, and linear low-density polyethylene. From the viewpoint of heat resistance of the laminate during heat sealing, the polyethylene layer containing high-density polyethylene as a main component is preferred.
[0082] From the viewpoint of reducing the environmental load, the polyethylene layer in the first resin layer may contain biomass polyethylene as the polyethylene. Examples of biomass polyethylene include biomass high density polyethylene, biomass medium density polyethylene, biomass low density polyethylene, and biomass linear low density polyethylene, and among these, biomass high density polyethylene is preferred.
[0083] The MFR of the polyethylene in the first resin layer is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more, from the viewpoint of film-forming property and processability. The MFR of the polyethylene is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less, from the viewpoint of film-forming property and processability. The MFR of the polyethylene is measured by the A method at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014.
[0084] From the viewpoint of heat resistance, the melting point (Tm) of the polyethylene in the first resin layer is preferably 100° C. or higher, more preferably 105° C. or higher, even more preferably 110° C. or higher, particularly preferably 120° C. or higher, and preferably 140° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0085] The polyethylene content in the polyethylene layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more.
[0086] The polyethylene layer in the first resin layer may further contain modified polyethylene from the viewpoint of adhesion to the heteroatom-containing resin layer. Examples of modified polyethylene include polyethylene modified with unsaturated carboxylic acids such as maleic acid and fumaric acid, or their acid anhydrides, esters, or metal salts, particularly graft modified polyethylene. The modified polyethylene may be modified high density polyethylene or maleic anhydride graft modified high density polyethylene. The modified polyethylene may be a biomass material from the viewpoint of reducing the environmental load.
[0087] From the viewpoint of film-forming property and processability, the MFR of the modified polyethylene is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the MFR of the modified polyethylene is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of the modified polyethylene is measured by the A method at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014.
[0088] The content of the modified polyethylene in the polyethylene layer is preferably less than 50% by mass, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less. The content of the modified polyethylene in the polyethylene layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more.
[0089] ((Polypropylene layer)) The polypropylene layer in the first resin layer contains polypropylene as a main component. The laminate including the polypropylene layer has excellent oil resistance.
[0090] The polypropylene may be any one of a propylene homopolymer (homopolypropylene), a propylene random copolymer (random polypropylene) and a propylene block copolymer (block polypropylene), or may be a mixture of two or more selected from these. As the polypropylene, from the viewpoint of reducing the environmental load, biomass polypropylene or mechanically recycled or chemically recycled polypropylene may be used.
[0091] A propylene homopolymer is a polymer of propylene alone. A propylene random copolymer is a random copolymer of propylene and an α-olefin other than propylene. A propylene block copolymer is a copolymer having at least a polymer block of propylene and at least a polymer block of an α-olefin other than propylene.
[0092] Examples of α-olefins other than propylene include α-olefins having 2 to 20 carbon atoms, specifically, ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene.
[0093] Among polypropylenes, propylene random copolymers are preferred from the viewpoint of transparency. When the rigidity and heat resistance of the packaging bag are important, propylene homopolymers are preferred. When the impact resistance of the packaging bag is important, propylene block copolymers are preferred.
[0094] The density of polypropylene is, for example, 0.88 g / cm 3 More than 0.92g / cm 3 The density of polypropylene is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.).
[0095] From the viewpoint of heat resistance, the melting point (Tm) of polypropylene is preferably 120° C. or higher, more preferably 130° C. or higher, and even more preferably 150° C. or higher. The Tm of polypropylene is preferably 170° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0096] The polypropylene content in the polypropylene layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0097] (adhesive layer) In one embodiment, the adhesive layer in the first resin layer is an adhesive layer made of an adhesive. The adhesive may be any of a one-component curing adhesive, a two-component curing adhesive, and a non-curing adhesive. The adhesive may be a solventless adhesive or a solvent-based adhesive.
[0098] Examples of solvent-free adhesives, i.e., non-solvent laminate adhesives, include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives. Among these, urethane adhesives are preferred, and two-liquid curing urethane adhesives are more preferred. Examples of solvent-based adhesives include rubber adhesives, vinyl adhesives, olefin adhesives, silicone adhesives, epoxy adhesives, phenol adhesives, and urethane adhesives.
[0099] The thickness of the adhesive layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.5 μm or more. The thickness of the adhesive layer is preferably 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less.
[0100] In one embodiment, the first resin layer may be a laminated film having a heteroatom-containing resin layer, an adhesive layer, and a heteroatom-containing resin layer in this order in the thickness direction. In one embodiment, the laminated film may be produced by laminating two or more films (e.g., heteroatom-containing resin films such as PET films) corresponding to the heteroatom-containing resin layer by a non-solvent lamination method using a solvent-free adhesive, or by laminating them by a dry lamination method using a solvent-based adhesive.
[0101] <Second resin layer> The second resin layer is a sealant layer containing polyolefin as a main component. When a packaging bag is produced using the laminate of the present disclosure, the second resin layer is a layer facing the storage space of the packaging bag. In one embodiment, the packaging bag obtained by separating and removing the first resin layer from the laminate can be made into a mono-material bag.
[0102] Examples of polyolefins include polyethylene, polypropylene, and polymethylpentene. Among these, polyethylene and polypropylene are preferred, and polyethylene is more preferred. The polyolefin may be a biomass polyolefin from the viewpoint of reducing the environmental load.
[0103] The MFR of the polyolefin in the second resin layer is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more, from the viewpoint of film-forming property and processability. The MFR of the polyolefin is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less, from the viewpoint of film-forming property and processability. The MFR of the polyolefin is measured by the A method under a load of 2.16 kg in accordance with JIS K7210-1:2014. The measurement temperature of the MFR is set according to the melting point of the polyolefin, and is 190 ° C. for polyethylene and 230 ° C. for polypropylene.
[0104] The content of polyolefin in the second resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more, based on the mass of the second resin layer. A laminate having such a second resin layer has excellent recyclability. Specifically, a sealant film corresponding to the second resin layer after peeling and removing the first resin layer from the laminate has excellent recyclability.
[0105] In one embodiment, the above "polyolefin content in the second resin layer" can be read as "polyethylene content in the second resin layer" or "polypropylene content in the second resin layer."
[0106] In one embodiment, the second resin layer contains polyethylene as a main component. Examples of polyethylene include high density polyethylene, medium density polyethylene, low density polyethylene, and linear low density polyethylene, and from the viewpoint of heat sealability, low density polyethylene and linear low density polyethylene are preferred. From the viewpoint of reducing environmental load, the polyethylene may be biomass polyethylene.
[0107] From the viewpoint of a balance between heat resistance and heat sealability, the melting point (Tm) of the polyethylene in the second resin layer is preferably 80° C. or higher, more preferably 85° C. or higher, and preferably 140° C. or lower, more preferably 130° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0108] In one embodiment, the second resin layer contains polypropylene as a main component. A laminate including such a second resin layer has excellent oil resistance.
[0109] Examples of polypropylene include propylene homopolymers, propylene random copolymers such as propylene-α-olefin random copolymers, and propylene block copolymers such as propylene-α-olefin block copolymers. Details of the α-olefins are as described above. From the viewpoint of reducing the environmental load, biomass polypropylene and mechanically recycled or chemically recycled polypropylene may be used as the polypropylene.
[0110] From the viewpoint of heat sealability, the density of the polypropylene in the second resin layer is, for example, 0.88 g / cm 3 More than 0.92g / cm 3The density of polypropylene is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.).
[0111] From the viewpoint of a balance between heat resistance and heat sealability, the melting point (Tm) of the polypropylene in the second resin layer is preferably 120° C. or higher, more preferably 125° C. or higher, even more preferably 130° C. or higher, and preferably 160° C. or lower, more preferably 155° C. or lower, even more preferably 150° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0112] The second resin layer may contain the above-mentioned additives.
[0113] In one embodiment, the biomass degree of the second resin layer is preferably 10% or more, more preferably 20% or more, even more preferably 30% or more, even more preferably 40% or more, particularly preferably 50% or more, and may be 99% or less, 90% or less, 80% or less, or 70% or less. Such a laminate or a packaging bag including the laminate can reduce the environmental load. However, compared with conventional resin materials derived from fossil fuels, biomass materials may have a broader molecular weight distribution and contain a large amount of low molecular weight components. Since the second resin layer may come into contact with an item contained in the packaging bag, depending on the type of the item (e.g., semiconductor products and related parts, etc.), it may be better for the second resin layer not to contain a biomass material. In such a case, in one embodiment, the biomass degree of the second resin layer may be less than 10%, may be 5% or less, may be 3% or less, or may be 1% or less.
[0114] From the viewpoints of strength and heat sealability, the thickness of the second resin layer is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and particularly preferably 30 μm or more. From the viewpoint of processability, the thickness of the second resin layer is preferably 250 μm or less, more preferably 200 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less.
[0115] In one embodiment, the second resin layer includes at least a heat-sealable resin layer containing polyolefin such as polyethylene and polypropylene as a main component as a surface layer of the laminate. In one embodiment, the heat-sealable resin layer in the second resin layer is in contact with the first resin layer.
[0116] In one embodiment, the second resin layer has a density of 0.909 g / cm 3 The second resin layer includes at least the following polyethylene layer: In one embodiment, the polyethylene layer in the second resin layer is in contact with the first resin layer.
[0117] In one embodiment, the second resin layer has a density of 0.909 g / cm 3 The laminate includes a polyethylene layer and a heat-sealable resin layer containing polyethylene as a main component as a surface layer of the laminate. In one embodiment, the polyethylene layer in the second resin layer is in contact with the first resin layer.
[0118] In one embodiment, the second resin layer has a density of 0.909 g / cm 3 The heat-sealable resin layer further includes an intermediate layer containing polyethylene as a main component between the polyethylene layer and the heat-sealable resin layer containing polyethylene as a main component.
[0119] In one embodiment, the second resin layer comprises an extruded resin layer containing polyethylene as a main component and a heat-sealable resin layer containing polyethylene as a main component. In this embodiment, a film corresponding to the first resin layer and a heat-sealable film corresponding to the heat-sealable resin layer are laminated via the extruded resin layer. That is, the laminate of this embodiment comprises an extruded resin layer between the first resin layer and the heat-sealable resin layer.
[0120] (Polyethylene layer) In one embodiment, the second resin layer has a density of 0.909 g / cm 3The laminate having such a polyethylene layer can suppress lifting of the first resin layer from the second resin layer during the production of the laminate, and has good peel strength between the first resin layer and the second resin layer. 3 The following polyethylene layer has an excellent balance of adhesion to the heteroatom-containing resin layer and peelability.
[0121] The density of the polyethylene layer is preferably 0.908 g / cm 3 Less than or equal to 0.907 g / cm 3 More preferably, 0.906 g / cm 3 More preferably, 0.905 g / cm 3 Below 0.904 g / cm, particularly preferably 0.904 g / cm 3 The density of the polyethylene layer is preferably 0.860 g / cm 3 More preferably, 0.870 g / cm 3 More preferably, 0.880 g / cm 3 More preferably, 0.890 g / cm 3 More preferably, 0.895 g / cm 3 The density of the polyethylene layer is measured in accordance with JIS K7112:1999, Method D (density gradient tube method, 23° C.).
[0122] In one embodiment, the polyethylene layer has a density of 0.909 g / cm 3 The polyethylene used is preferably polyethylene having a density of 0.909 g / cm 3The following linear low density polyethylene is contained as a main component. Examples of linear low density polyethylene include ethylene-1-butene copolymer (C4-LLDPE) in which the comonomer is at least 1-butene, ethylene-1-hexene copolymer (C6-LLDPE) in which the comonomer is at least 1-hexene, and ethylene-1-octene copolymer (C8-LLDPE) in which the comonomer is at least 1-octene. In these copolymers, the comonomer is not limited to the above-mentioned one, and further comonomers may be used. The polyethylene may be biomass polyethylene from the viewpoint of reducing the environmental load.
[0123] The density of the polyethylene, such as linear low density polyethylene, is preferably 0.908 g / cm 3 Less than or equal to 0.907 g / cm 3 More preferably, 0.906 g / cm 3 More preferably, 0.905 g / cm 3 Below 0.904 g / cm, particularly preferably 0.904 g / cm 3 The density of the polyethylene is preferably 0.860 g / cm 3 More preferably, 0.870 g / cm 3 More preferably, 0.880 g / cm 3 More preferably, 0.890 g / cm 3 More preferably, 0.895 g / cm 3 That's all.
[0124] Density is 0.909g / cm 3 From the viewpoint of film-forming property and processability, the MFR of the following polyethylene is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and further preferably 0.5 g / 10 min or more. 3From the viewpoint of film-forming property and processability, the MFR of the following polyethylene is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, further preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of polyethylene is measured by Method A at a temperature of 190° C. and a load of 2.16 kg in accordance with JIS K7210-1:2014.
[0125] Density is 0.909g / cm 3 The polyethylene may be a metallocene-based linear low-density polyethylene. A metallocene-based linear low-density polyethylene is a metallocene-based ethylene-α-olefin copolymer, i.e., an ethylene-α-olefin copolymer produced using a metallocene catalyst, and has a generally linear molecular structure.
[0126] Examples of the α-olefins copolymerized with ethylene include α-olefins having 3 to 12 carbon atoms, specifically propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 4-methyl-1-pentene, 1-decene, and 1-dodecene. Among these, α-olefins having 3 to 8 carbon atoms are preferred. Examples of linear low density polyethylene include C4-LLDPE, C6-LLDPE, and C8-LLDPE.
[0127] The melting point (Tm) of the metallocene-based linear low-density polyethylene is preferably 110° C. or lower, more preferably 105° C. or lower, and even more preferably 100° C. or lower. The melting point (Tm) of the metallocene-based linear low-density polyethylene is preferably 80° C. or higher, more preferably 85° C. or higher, and even more preferably 88° C. or higher. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0128] Among the metallocene-based linear low density polyethylenes, resins called metallocene-based ethylene plastomers are preferred. Specifically, metallocene-based ethylene plastomers are a type of copolymer of ethylene and α-olefin (ethylene-α-olefin copolymer) obtained by a metallocene catalyst. Metallocene-based ethylene plastomers have a density in the range called ultra-low density, which is relatively low among low densities, a uniform polymer distribution indexed by a narrow molecular weight distribution (Mw / Mn) derived from a polymerization method using a metallocene catalyst, which is a catalyst having uniform catalytic activity sites, and plastomer properties.
[0129] As the metallocene-based ethylene plastomer, a commercially available product may be used. For example, the commercially available product may be selected from the "Kernel (registered trademark)" series manufactured by Japan Polyethylene. For example, "KF260T", "KF360T" and "KS340T" may be mentioned.
[0130] Density is 0.909g / cm 3 The ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) of the following polyethylene is preferably 3.5 or less, more preferably 3.3 or less, and even more preferably 3.0 or less. The ratio (Mw / Mn) is 1.0 or more, preferably 1.5 or more, more preferably 1.8 or more, and even more preferably 2.1 or more.
[0131] Mw / Mn is defined as the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) measured by gel permeation chromatography (GPC). Mw and Mn are measured by the following method. Apparatus: Waters GPC 150C type detector: MIRAN 1A infrared spectrophotometer (measurement wavelength, 3.42 μm) Column: Showa Denko AD806M / S x 3 [The column is calibrated by measuring Tosoh monodisperse polystyrene (A500, A2500, F1, F2, F4, F10, F20, F40, F288, each 0.5 mg / ml solution) and approximating the logarithm of the elution volume and molecular weight with a quadratic equation. The molecular weight of the sample is converted to polyethylene using the viscosity equation for polystyrene and polyethylene. The coefficients of the viscosity equation for polystyrene are α=0.723, logK=-3.967, and for polyethylene, α=0.707, logK=-3.407.] Measurement temperature: 140℃ Injection amount: 0.2ml Concentration: 20mg / 10mL Solvent: ortho-dichlorobenzene Flow rate: 1.0ml / min
[0132] The density of the polyethylene layer is 0.909 g / cm 3 The content of the following polyethylene is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0133] The polyethylene layer may contain the above-mentioned resin materials other than polyethylene. The polyethylene layer may contain the additives described above.
[0134] Density is 0.909g / cm 3 From the viewpoint of peel strength, the thickness of the following polyethylene layer is preferably 0.5 μm or more, more preferably 1 μm or more, further preferably 3 μm or more, and particularly preferably 5 μm or more. 3 From the viewpoint of processability in film formation, the thickness of the following polyethylene layer is preferably 50 μm or less, more preferably 40 μm or less, further preferably 30 μm or less, and particularly preferably 20 μm or less.
[0135] (thermal adhesive resin layer) In one embodiment, the second resin layer is provided as a surface layer of the laminate, which is a heat-sealable resin layer containing polyolefins such as polyethylene and polypropylene as main components. Such a heat-sealable resin layer functions as a sealing layer in a packaging bag including the laminate. When a packaging bag is produced using the laminate of the present disclosure, the heat-sealable resin layer is a layer facing the storage space of the packaging bag.
[0136] In one embodiment, the second resin layer comprises a heat-sealable resin layer. In one embodiment, 0.909 g / cm 3 The polyethylene layer having the following density is one surface layer of the second resin layer, and the heat-fusible resin layer is the other surface layer of the second resin layer.
[0137] Examples of polyolefins include polyethylene and polypropylene, and polyethylene is preferred. Examples of polyethylene include linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, and ethylene-(meth)acrylic acid ester copolymer. From the viewpoint of reducing environmental load, the polyethylene may be biomass polyethylene.
[0138] From the viewpoint of heat sealability, the heat-fusible resin layer preferably contains, as a main component, at least one polyethylene selected from linear low-density polyethylene and low-density polyethylene, such as C4-LLDPE, C6-LLDPE, and C8-LLDPE.
[0139] The total content of the linear low-density polyethylene and the low-density polyethylene in the heat-sealable resin layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0140] In one embodiment, the heat-sealable resin layer contains linear low-density polyethylene and low-density polyethylene. Such a heat-sealable resin layer has an excellent balance between heat sealability and low contamination (suppression of outgassing) of the article contained in the packaging bag.
[0141] The content ratio (LLDPE:LDPE) of linear low density polyethylene (LLDPE) to low density polyethylene (LDPE) in the heat-sealable resin layer is preferably 5:95 to 95:5, more preferably 10:90 to 90:10, and further preferably 20:80 to 80:20, on a mass basis.
[0142] The numerical range of the MFR of the polyethylene in the heat-fusible resin layer may be the same as the numerical range of the MFR of the polyethylene contained in the polyethylene layer of the first resin layer.
[0143] From the viewpoint of heat sealability, the melting point (Tm) of the polyethylene in the heat-fusible resin layer is preferably 140° C. or lower, more preferably 130° C. or lower, even more preferably 125° C. or lower, and is preferably 90° C. or higher, more preferably 95° C. or higher, even more preferably 100° C. or higher. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0144] The heat-fusible resin layer may contain the above-mentioned additives.
[0145] The thickness of the heat-fusible resin layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 15 μm or more, still more preferably 20 μm or more, and particularly preferably 25 μm or more. The thickness of the heat-fusible resin layer is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, still more preferably 80 μm or less, and particularly preferably 60 μm or less.
[0146] (Middle class) The second resin layer has a density of 0.909 g / cm 3An intermediate layer containing polyethylene as a main component may be further provided between the polyethylene layer and the heat-sealable resin layer described below. From the viewpoint of the puncture resistance of the laminate, it is more preferable that the intermediate layer contains linear low-density polyethylene as a main component.
[0147] The polyethylene is preferably at least one selected from linear low-density polyethylene, low-density polyethylene, medium-density polyethylene, and high-density polyethylene, and from the viewpoint of heat sealability, more preferably at least one selected from linear low-density polyethylene and low-density polyethylene, and even more preferably linear low-density polyethylene. Examples of linear low-density polyethylene include C4-LLDPE, C6-LLDPE, and C8-LLDPE. From the viewpoint of reducing environmental load, the polyethylene may be biomass polyethylene.
[0148] The density of the polyethylene in the intermediate layer is preferably 0.925 g / cm 3 More preferably, 0.928 g / cm 3 More preferably, 0.930 g / cm 3 The laminate having such an intermediate layer has excellent puncture resistance. The density of the polyethylene in the intermediate layer is preferably 0.932 g / cm 3 The following is the result.
[0149] From the viewpoint of film-forming property and processability, the MFR of the polyethylene in the intermediate layer is preferably 0.1 g / 10 min or more, more preferably 0.3 g / 10 min or more, and even more preferably 0.5 g / 10 min or more. From the viewpoint of film-forming property and processability, the MFR of the polyethylene in the intermediate layer is preferably 30 g / 10 min or less, more preferably 20 g / 10 min or less, even more preferably 10 g / 10 min or less, and particularly preferably 5 g / 10 min or less. The MFR of the polyethylene is measured by the A method in accordance with JIS K7210-1:2014 under the conditions of a temperature of 190°C and a load of 2.16 kg.
[0150] From the viewpoint of heat resistance, the melting point (Tm) of the polyethylene in the intermediate layer is preferably 100° C. or higher, more preferably 105° C. or higher, even more preferably 110° C. or higher, particularly preferably 120° C. or higher, and preferably 140° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0151] From the viewpoint of the puncture resistance and recyclability of the laminate, the polyethylene content in the intermediate layer is preferably more than 50% by mass, more preferably 60% by mass or more, even more preferably 70% by mass or more, still more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0152] The intermediate layer may contain the above-mentioned resin material. The intermediate layer may contain the above-mentioned additives.
[0153] The thickness of the intermediate layer is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, and particularly preferably 10 μm or more. The thickness of the intermediate layer is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 25 μm or less.
[0154] (Extruded resin layer) The extruded resin layer contains polyethylene as a main component. From the viewpoint of adhesiveness, the polyethylene constituting the extruded resin layer is preferably at least one selected from low-density polyethylene and linear low-density polyethylene, and more preferably low-density polyethylene. From the viewpoint of reducing the environmental load, the polyethylene may be biomass polyethylene.
[0155] In one embodiment, the extruded resin layer functions as an adhesive layer between the heteroatom-containing resin film in the first resin layer and the heat-sealable film in the second resin layer. A laminate including such an extruded resin layer can have a high polyethylene content and is excellent in recyclability, and has an appropriate peel strength between the first resin layer and the second resin layer, resulting in excellent peelability of the first resin layer.
[0156] From the viewpoint of film-forming property and processability, the MFR of the polyethylene in the extruded resin layer is preferably 0.1 g / 10 min or more, more preferably 1 g / 10 min or more, even more preferably 3 g / 10 min or more, and preferably 30 g / 10 min or less, more preferably 25 g / 10 min or less, even more preferably 20 g / 10 min or less. The MFR of the polyethylene is measured by the A method in accordance with JIS K7210-1:2014 under the conditions of a temperature of 190° C. and a load of 2.16 kg.
[0157] From the viewpoint of a balance between heat resistance and adhesiveness, the melting point (Tm) of the polyethylene in the extruded resin layer is preferably 100° C. or higher, and preferably 140° C. or lower, more preferably 130° C. or lower, and further preferably 120° C. or lower. Tm is the melting peak temperature obtained by DSC in accordance with JIS K7121:2012.
[0158] The content of polyethylene in the extruded resin layer is preferably 80% by mass or more, more preferably 85% by mass or more, further preferably 90% by mass or more, and particularly preferably 95% by mass. A laminate including such an extruded resin layer has excellent recyclability.
[0159] The thickness of the extruded resin layer is preferably 5 μm or more, more preferably 10 μm or more. The thickness of the extruded resin layer is preferably 40 μm or less, more preferably 30 μm or less. A laminate including such an extruded resin layer has excellent interlayer adhesion and recyclability.
[0160] The extruded resin layer can be formed, for example, by melting polyethylene or a polyethylene resin composition and extruding it onto the film. The melting temperature at this time is preferably 280° C. or higher, more preferably 290° C. or higher, and preferably 340° C. or lower, more preferably 335° C. or lower.
[0161] <Design layer> The laminate of the present disclosure may further include a design layer such as a printed layer. The design layer has an image. Examples of the image include characters, figures, patterns, symbols, and combinations thereof. The image may include text information such as the product name, the name of the item in the packaging bag, the manufacturer, and the names of raw materials. The image may be a single, solid color (so-called solid image).
[0162] The design layer may be provided, for example, on the surface of the first resin layer. For example, the design layer may be provided on the surface (outer surface) of the first resin layer opposite to the surface facing the second resin layer.
[0163] In one embodiment, the design layer contains a colorant. Examples of colorants include pigments such as inorganic pigments and organic pigments, as well as dyes such as acid dyes, direct dyes, disperse dyes, oil-soluble dyes, metal-containing oil-soluble dyes, and sublimation dyes. Examples of colorants also include fluorescent materials such as ultraviolet emitting materials that emit fluorescence by absorbing ultraviolet light, and infrared emitting materials that emit fluorescence by absorbing infrared light.
[0164] The content of the colorant in the design layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. The content of the colorant in the design layer is preferably 90% by mass or less, more preferably 70% by mass or less, and even more preferably 50% by mass or less.
[0165] The design layer may contain the above-mentioned resin material and may also contain the above-mentioned additives. The content of the resin material in the design layer is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more. The content of the resin material in the design layer is preferably 99% by mass or less, more preferably 97% by mass or less, and even more preferably 95% by mass or less.
[0166] The design layer can be formed, for example, using an ink composition containing the above-mentioned components and, if necessary, a solvent. Methods for forming the design layer include, for example, gravure printing, offset printing, flexographic printing, screen printing, letterpress printing, and transfer printing. In one embodiment, from the viewpoint of reducing environmental load, flexographic printing may be used.
[0167] The thickness of the design layer is preferably 0.1 μm or more, more preferably 0.2 μm or more, and even more preferably 0.3 μm or more. The thickness of the design layer is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less.
[0168] <Configuration and manufacturing method of laminate> 1 to 5 and 10 show schematic cross-sectional views of a laminate according to one embodiment of the present disclosure. The laminate 1 in FIG. 1 includes a first resin layer 10 and a second resin layer 20 in this order in the thickness direction.
[0169] In the laminate 1 of FIG. 2, the second resin layer 20 has a density of 0.909 g / cm 3 1 except that it includes a polyethylene layer 22 and a thermally adhesive resin layer 24. The polyethylene layer 22 is in contact with the first resin layer 10.
[0170] The laminate 1 of Figure 3 is similar to the laminate 1 of Figure 2, except that the first resin layer 10 comprises a polyolefin layer 12 and a heteroatom-containing resin layer 14. The heteroatom-containing resin layer 14 is in contact with the polyethylene layer 22.
[0171] The laminate 1 in FIG. 4 is similar to the laminate 1 in FIG. 2, except that the second resin layer 20 further includes an intermediate layer 23 between the polyethylene layer 22 and the heat-fusible resin layer 24 .
[0172] The laminate 1 in FIG. 5 is similar to the laminate 1 in FIG. 4, except that the first resin layer 10 comprises a polyolefin layer 12 and a heteroatom-containing resin layer 14 .
[0173] The laminate 1 in Fig. 10 includes a first resin layer 10 and a second resin layer 20 in this order in the thickness direction. The first resin layer 10 includes a heteroatom-containing resin layer 14, an adhesive layer 16, and the heteroatom-containing resin layer 14. The second resin layer 20 includes an extruded resin layer 25 and a heat-sealable resin layer 24. A laminate film corresponding to the first resin layer 10 and a heat-sealable film corresponding to the heat-sealable resin layer 24 are laminated with the extruded resin layer 25 interposed therebetween.
[0174] The total thickness of the laminate of the present disclosure is preferably 15 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, even more preferably 40 μm or more, and particularly preferably 50 μm or more, from the viewpoint of the strength and heat resistance of the laminate. The total thickness of the laminate of the present disclosure is preferably 300 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, even more preferably 150 μm or less, and particularly preferably 100 μm or less, from the viewpoint of the processability of the laminate.
[0175] From the viewpoint of heat sealability, the laminate of the present disclosure is preferably an unstretched film. An unstretched film is a film that has not been stretched, for example, an extrusion-molded film that has not been stretched. The concept of the "unstretched film" includes not only a film that has not been stretched at all, but also a film that has been slightly stretched due to tension applied during film formation by an inflation method or the like.
[0176] The laminate of the present disclosure can be produced by a conventionally known method. The laminate is preferably a coextruded multilayer film, and can be produced, for example, by a coextrusion film forming method, more preferably by a T-die method or an inflation method. The laminate of the present disclosure can be formed, for example, by extruding the resin or resin composition forming each layer from an extruder in a molten state.
[0177] According to the above method, the first surface of the second resin layer that contacts the first resin layer is not directly exposed to the outside air during and after the production of the laminate. Therefore, it is possible to prevent foreign matter such as dust and dirt from adhering to the first surface of the second resin layer from the time of production of the laminate until the first resin layer is peeled off and removed. When the packaging bag is used, the first resin layer is peeled off and removed from the second resin layer of the laminate, thereby exposing the first surface of the second resin layer. This first surface is a clean surface in which the adhesion of foreign matter is prevented.
[0178] In one embodiment, the laminate of the present disclosure can be produced by laminating a film corresponding to the first resin layer and a heat-sealable film corresponding to the heat-sealable resin layer via an extruded resin layer containing polyethylene as a main component. Specifically, the laminate can be produced by laminating the above films together using a melt extrusion lamination method, particularly a sand lamination method, using a molten resin containing polyethylene as a main component. By carrying out lamination in a clean environment, contamination of the first surface of the second resin layer can be suppressed.
[0179] The heat-sealable film corresponding to the heat-sealable resin layer is preferably an unstretched resin film from the viewpoint of heat sealability. The resin film can be produced by, for example, a casting method, a T-die method, an inflation method, or the like.
[0180] The content of the polyolefin resin in the laminate of the present disclosure may be 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, or 90% by mass or more, based on the mass of the laminate. Such a laminate has excellent recyclability. The content of the polyolefin resin in the laminate of the present disclosure may be 99% by mass or less, 95% by mass or less, or 90% by mass or less, based on the mass of the laminate. The above "content of the polyolefin resin in the laminate" can be read as "content of the polyethylene resin in the laminate" or "content of the polypropylene resin in the laminate".
[0181] [Application] The laminate of the present disclosure can be suitably used as a packaging material for forming a packaging bag. The second resin layer in the laminate forms an inner surface (a surface that comes into contact with an article in the packaging bag) facing the storage space in the packaging bag.
[0182] A high level of cleanliness is required for an article used in a clean environment such as a clean room. A packaging bag containing the article is brought into the clean environment and opened. Therefore, a high level of cleanliness is also required for the packaging bag. That is, when the packaging bag containing the article is brought into the clean environment, it is necessary to prevent foreign matter such as dust and dirt from adhering to the surface of the packaging bag and the foreign matter from entering the clean environment together with the packaging bag. By using a packaging bag including the laminate of the present disclosure, the intrusion of such foreign matter can be prevented, for example, as follows.
[0183] First, an article is accommodated in the packaging bag of the present disclosure in a clean environment, and degassed by vacuum degassing or the like as necessary, and the opening of the packaging bag is sealed to obtain a package in which the article is accommodated in the packaging bag. Degassing is not limited to vacuum degassing as long as the gas in the packaging bag can be removed. For example, degassing may be performed by pressing the packaging bag from the outside using a pressing member. The package is brought into the front room of the clean environment. Here, the first resin layer (peeling film) in the laminate constituting the packaging bag is peeled off and removed. This exposes the first surface of the second resin layer (sealant film) in the laminate constituting the packaging bag. As described above, the first surface of the second resin layer is a clean surface in which adhesion of foreign matter is suppressed. The packaging bag obtained by peeling off and removing the first resin layer has a small amount of foreign matter attached to its surface. Such a packaging bag is brought into the clean environment. In the clean environment, the packaging bag is opened to take out the article and use it. In this way, intrusion of foreign matter into the clean environment together with the packaging bag is suppressed.
[0184] According to the above configuration, the packaging bag of the present disclosure does not need to be configured as a double-ply bag having at least an inner bag and an outer bag, or a triple-ply or more bag. However, there is no restriction on using the packaging bag of the present disclosure as an outer bag in a double-ply bag or a triple-ply or more bag.
[0185] Examples of the goods to be stored in the packaging bag include semiconductor products such as ICs and LSIs, semiconductor-related parts such as valves for semiconductor devices and filters for semiconductor manufacturing, precision machinery, magnetic disks, silicon wafers, O-rings, bellows, pharmaceutical products, products for regenerative medicine, and medicinal liquid products such as diluents for blood cell testing devices and artificial dialysis fluids. Examples of the goods to be stored in the packaging bag include dustproof clothing, dustproof gloves, and tools used in clean environments.
[0186] The packaging bag of the present disclosure includes the laminate of the present disclosure. The packaging bag of the present disclosure has a seal portion formed by, for example, fusing together the second resin layers in the laminate. In one embodiment, the packaging bag of the present disclosure includes a top sheet constituting the top surface and a back sheet constituting the back surface. The top sheet may be made of one laminate of the present disclosure, and the back sheet may be made of another laminate of the present disclosure. The top sheet and the back sheet may be integrated together, or may be made of one laminate of the present disclosure. The top sheet and the back sheet may be made of one tubular laminate of the present disclosure.
[0187] A packaging bag usually has a heat-sealed portion (heat-sealed portion, hereinafter also referred to as "sealed portion"). Examples of heat-sealing methods include bar sealing, rotary roll sealing, belt sealing, impulse sealing, high-frequency sealing, and ultrasonic sealing.
[0188] Examples of packaging bags include packaging bags of various shapes such as a standing pouch type, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type (pillow seal type), a pleated seal type, a flat bottom seal type, a square bottom seal type, and a gusset type. The planar shape of the packaging bag may be, for example, rectangular or a shape other than rectangular, such as a circle.
[0189] An example of how to produce a packaging bag using the laminate of the present disclosure will be described. Two laminates are prepared. The two laminates are stacked with the second resin layers facing each other. Next, heat seal parts are formed on the three sides of the outer peripheral edge of the laminate, that is, the left and right sides and the bottom. In this way, a packaging bag having an opening on one side is obtained.
[0190] Instead of using two sheets of the laminate of the present disclosure, one sheet of the laminate of the present disclosure may be prepared, folded and stacked so that the second surfaces of the second resin layers of the laminate face each other, and then heat-sealed portions may be formed on both the left and right outer peripheral edges to produce a packaging bag. In this way, a packaging bag having an opening on one side is obtained. In this case, a heat-sealed portion may also be formed on the folded lower portion, and further, the lower portion of the lower heat-sealed portion may be cut and removed. This allows the first resin layer to be peeled off and removed from both the front sheet and back sheet of the packaging bag.
[0191] The packaging bag may be produced as follows. The laminate of the present disclosure is formed by an inflation method to obtain a tubular film. Both ends of the tubular film in the width direction perpendicular to the flow direction are cut along the flow direction. Next, both ends of the film in the width direction are heat sealed along the flow direction, and the portions extending in the width direction of the film are heat sealed at regular intervals in the flow direction. Next, the film is cut along the flow direction at the center of the film in the width direction, and the film is cut along the width direction at the heat-sealed portions extending in the width direction. FIG. 9A shows a front view of the film, with the hatched portions indicating the heat-sealed portions and the dotted lines indicating the portions to be cut. In this manner, a plurality of packaging bags having an opening on one side are obtained.
[0192] The packaging bag may be produced as follows. Both widthwise ends of a tubular film are cut along the machine direction. Next, one widthwise end of the film is heat-sealed along the machine direction, and a portion extending in the widthwise direction of the film is heat-sealed at regular intervals in the machine direction. Next, the film is cut along the widthwise direction at the heat-sealed portion extending in the widthwise direction (see FIG. 9B). In this manner, a plurality of packaging bags having an opening on one side are obtained.
[0193] The packaging bag may be produced as follows. Both ends in the width direction of the tubular film are cut along the flow direction. Next, the portions extending in the flow direction at the center of the width direction of the film are heat-sealed, or the portions extending in the flow direction of the film are heat-sealed at regular intervals in the width direction, and the portions extending in the width direction of the film are heat-sealed at regular intervals in the flow direction. The portions heat-sealed along the flow direction of the film may be, for example, one or more rows and five or less rows, or one or more rows and three or less rows. Next, the film is cut along the flow direction at the heat-sealed portions extending in the flow direction, and the film is cut along the width direction at the heat-sealed portions extending in the width direction (see Figs. 9C and 9D). In this manner, a plurality of packaging bags having an opening on one side are obtained.
[0194] An article is inserted through the opening of the unheat-sealed portion of the packaging bag produced above. The opening of the packaging bag is then heat-sealed to form a heat-sealed portion, thereby obtaining a package in which the article is housed in the packaging bag.
[0195] 6a is a cross-sectional view showing one embodiment of the packaging bag of the present disclosure. The sealed portion of the packaging bag 50 is formed by overlapping and heat-sealing a laminate 1 including a first resin layer 10 and a second resin layer 20.
[0196] 6b is a cross-sectional view showing one embodiment of a usage form of the packaging bag of the present disclosure. For example, the first resin layers 10, 10 are peeled off from the second resin layers 20, 20 of the packaging bag 50, respectively, immediately before being brought into a clean room.
[0197] The packaging bag may have an easy-open portion. Examples of the easy-open portion include a notch portion that serves as a starting point for tearing the packaging bag, and an easy-open line formed by laser processing or a cutter as a path for tearing the packaging bag.
[0198] FIG. 7 is a front view showing one embodiment of the packaging bag of the present disclosure. Hereinafter, an example of the packaging bag will be described with reference to FIG. 7. The packaging bag 50 of FIG. 7 has a storage section 50a for storing an item. The packaging bag 50 includes an upper section 51, a lower section 52, and side sections 53, 53, and has a substantially rectangular outline in a front view. Note that names such as "upper section," "lower section," and "side section," as well as terms such as "upper" and "lower" merely relatively indicate the positions and directions of the packaging bag 50 and its components. The posture, etc. of the packaging bag 50 during transportation or use are not limited by the names and terms in this specification.
[0199] As shown in FIG. 7, the packaging bag 50 includes a top sheet 54 constituting the top surface and a back sheet 55 constituting the back surface. In the packaging bag 50 shown in FIG. 7, the top sheet 54 and the back sheet 55 are each formed of a single laminate. Although not shown, in the packaging bag 50, the top sheet 54 and the back sheet 55 may be integrated or may be formed of a single laminate. In this case, the laminate is folded back at the lower portion 52 so that the second resin layer forms the inner surface of the packaging bag 50. In this case, the packaging bag 50 has a seal portion extending along three sides of the packaging bag 50.
[0200] The inner surfaces of the top sheet 54 and the back sheet 55 are joined together by a sealed portion. In the front view of the packaging bag 50 shown in Fig. 7, the sealed portion is hatched. The sealed portion is the portion where the sealant layers of the laminate are joined together.
[0201] 7, the packaging bag 50 has heat-sealed portions extending along the four sides of the packaging bag 50. The sealed portions include an upper sealed portion 51a extending along the upper portion 51, a pair of side sealed portions 53a, 53a extending along a pair of side portions 53, 53, and a lower sealed portion 52a extending along the lower portion 52. In the packaging bag 50 before an article is contained therein (a state in which no article is contained therein), an opening (not shown) is formed in the upper portion 51 of the packaging bag 50. After an article is contained in the packaging bag 50, the inner surface of the top sheet 54 and the inner surface of the back sheet 55 are joined at the upper portion 51 to form the upper sealed portion 51a and seal the packaging bag 50.
[0202] The upper seal portion 51a, the side seal portions 53a, 53a and the lower seal portion 52a are seal portions formed by joining the inner surface of the top sheet 54 and the inner surface of the back sheet 55 together.
[0203] There is no particular limitation on the method for forming the sealed portion as long as it is possible to join opposing sheets 54, 55 together to seal packaging bag 50. For example, the sealed portion is formed by melting the inner surfaces of the sheets by heating or the like and fusing the inner surfaces together, that is, by heat sealing.
[0204] In one embodiment, the laminate constituting the packaging bag has a half-cut line. The half-cut line is a cut line that extends from the surface of the first resin layer constituting the laminate to the interface between the first resin layer and the second resin layer, but does not penetrate the laminate. Starting from the half-cut line, the first resin layer in the laminate can be easily peeled off and removed by hand.
[0205] The position where the half-cut line is formed is not particularly limited. For example, in the case of a packaging bag having a rectangular planar shape, it is preferable to provide the half-cut line at at least one corner of the packaging bag. It is preferable that the half-cut line is formed on both the top sheet and the back sheet of the packaging bag. In one embodiment, the half-cut line extends from the side outer edge to the lower outer edge of the top sheet and the back sheet at the corners of the sheets.
[0206] The half-cut line can be formed, for example, by mechanically making a cut in the thickness direction of the laminate using a cutter or the like, or by irradiating the laminate with a laser.
[0207] The half cut line will be specifically described with reference to FIG. 7 and FIG. As shown in Fig. 7, a half-cut line 60 is formed at one corner of the sealed portion of packaging bag 50. As shown in Fig. 7, half-cut line 60 extends from the outer edge of side portion 53 to the outer edge of lower portion 52 of packaging bag 50. Half-cut line 60 is formed on both the front and back surfaces of packaging bag 50, i.e., on top sheet 54 and back sheet 55. FIG. 8 is an enlarged view of a half-cut line provided in a laminate that constitutes a packaging bag.
[0208] Since half-cut lines 60 are formed on both the front and back sides of the packaging bag 50, a corner of the packaging bag 50 can be folded along the half-cut line 60 formed on one side just before the packaging bag 50 containing an article is brought into a clean room. This allows the first resin layer 10 to be easily peeled off from the second resin layer 20. Next, the other first resin layer 10 can be peeled off from the second resin layer 20 by similarly folding a corner of the packaging bag 50 along the half-cut line 60 formed on the other side.
[0209] [Aspects of the present disclosure] The present disclosure relates to, for example, the following [1] to
[17] . [1] A laminate comprising at least a first resin layer and a second resin layer, wherein the first resin layer is provided so as to be peelable from the second resin layer, the second resin layer is a sealant layer containing polyolefin as a main component, and at least one resin layer selected from the first resin layer and the second resin layer contains at least a biomass-derived resin material. [2] The laminate according to [1], wherein the first resin layer comprises at least a heteroatom-containing resin layer containing a heteroatom-containing resin as a main component, and the heteroatom-containing resin layer is in contact with the second resin layer. [3] The laminate according to [2], wherein at least a portion of the heteroatom-containing resin is a biomass-derived resin material. [4] The laminate according to [2] or [3] above, wherein the heteroatom-containing resin comprises at least one selected from the group consisting of polyamide, ethylene-vinyl alcohol copolymer, polyester, and polyvinyl alcohol. [5] The laminate according to any one of [2] to [4] above, wherein the first resin layer further comprises a polyolefin layer containing a polyolefin as a main component. [6] The laminate according to [5], wherein at least a portion of the polyolefin is a biomass-derived resin material. [7] The laminate according to [5] or [6], wherein the polyolefin layer further contains a modified polyolefin in addition to the polyolefin. [8] The laminate described in any one of [1] to [7], wherein the second resin layer comprises a heat-sealable resin layer containing polyolefin as a main component as one surface layer of the laminate. [9] The laminate according to [8], wherein the heat-sealable resin layer contains at least one type of polyethylene selected from linear low-density polyethylene and low-density polyethylene as a main component.
[10] The second resin layer has a density of 0.909 g / cm 3The laminate according to any one of the above [2] to [7], comprising: a polyethylene layer; and a heat-sealable resin layer containing polyethylene as a main component as one surface layer of the laminate, wherein the polyethylene layer in the second resin layer is in contact with the heteroatom-containing resin layer in the first resin layer.
[11] The second resin layer has a density of 0.909 g / cm 3 The laminate according to
[10] above, further comprising an intermediate layer containing linear low density polyethylene as a main component between the polyethylene layer and the heat-sealable resin layer.
[12] The laminate according to any one of the above [1] to
[11] , having a biomass ratio of 3% or more.
[13] The laminate according to any one of the above [1] to
[12] , wherein the first resin layer has a biomass content of 10% or more.
[14] The laminate according to any one of [1] to
[13] , wherein a peel strength between the first resin layer and the second resin layer, measured under conditions of a peel angle of 180 degrees and a test speed of 50 mm / min, is 1.0 N / 15 mm width or less.
[15] The laminate according to any one of the above [1] to
[14] , which is a coextruded multilayer film.
[16] A packaging bag comprising the laminate according to any one of [1] to
[15] above.
[17] The packaging bag according to
[16] , having a seal portion formed by fusing the second resin layers in the laminate. EXAMPLES
[0210] The laminate of the present disclosure will be described more specifically based on examples, but the laminate of the present disclosure is not limited to the examples in any way.
[0211] [Raw material ingredients] The components used in the following examples and comparative examples are shown below. Biomass polyamide (bPA) Toray, Amilan CM2001L, Polyamide 610, Melting point: 225℃, density: 1.08g / cm 3, Biomass content: 59.5% Biomass polyamide (bPA) Arkema, RILSAN BESN P20 TL, Polyamide 11, Melting point: 185℃, density: 1.04g / cm 3 , Biomass content: 70% Biomass polyamide (bPA) Daicel-Evonik, VESTAMID Terra DS22, Polyamide 1010, Melting point: 199℃, density: 1.04g / cm 3 , MFR: 2.0g / 10min, Biomass content: 100% Polyamide (PA) UBE, 5033B, polyamide 6 / 66 copolymer, Melting point: 197°C, density: 1.14g / cm 3 , MFR: 4.0g / 10min (Temperature 235℃, Load 2.16kg) High density polyethylene (HDPE) Made by Prime Polymer, HZ5000SF Melting point: 132°C, density: 0.954g / cm 3 , MFR: 0.66g / 10min Biomass High Density Polyethylene (bHDPE) Manufactured by Braskem, GreenPE SGF4950, Melting point: 133℃, density: 0.956g / cm 3 , MFR:0.34g / 10min, Biomass content: 96% · Linear low density polyethylene (LLDPE) Prime Polymer, SP0511, C6-LLDPE, Melting point: 98℃, density: 0.901g / cm 3 , MFR:1.2g / 10min · Linear low density polyethylene (LLDPE) Prime Polymer, UZ3500ZA, C4-LLDPE, Melting point: 120℃, density: 0.921g / cm 3, MFR:2.1g / 10min · Linear low density polyethylene (LLDPE) Prime Polymer, UZ2021L, C6-LLDPE, Melting point: 120℃, density: 0.919g / cm 3 , MFR: 2.0g / 10min · Linear low density polyethylene (LLDPE) Prime Polymer, UZ3520L, C6-LLDPE, Melting point: 124℃, density: 0.931g / cm 3 , MFR:2.1g / 10min ·Low Density Polyethylene (LDPE) Ube Maruzen polyethylene, B128, Melting point: 114℃, density: 0.928g / cm 3 , MFR: 1.0g / 10min Maleic anhydride grafted high density polyethylene (mHDPE) Dow Chemical, BYNEL 40E 1053, adhesive resin, Melting point: 130℃, density: 0.960g / cm 3 , MFR: 2.0g / 10min
[0212] [Example 1] A mixture of bPA (Amilan CM2001L), LLDPE (SP0511), and 70% by weight of LDPE (B128) and 30% by weight of LLDPE (UZ3500ZA) was co-extruded by blown film extrusion to obtain a laminate with a total thickness of 70 μm, including a 15 μm thick PA layer, a 15 μm thick LLDPE layer, and a 40 μm thick polyethylene blend layer. The mass % of a mixture indicates the content of each component in the mixture.
[0213] [Example 2] A mixture of 80% by mass of HDPE (HZ5000SF) and 20% by mass of acid-modified polyethylene (BYNEL 40E 1053), bPA (Amilan CM2001L), LLDPE (SP0511), 30% by mass of LDPE (B128) and 70% by mass of LLDPE (UZ2021L) was co-extruded by inflation method. In this way, a laminate with a total thickness of 75 μm was obtained, which includes a 15 μm thick HDPE blend layer, a 5 μm thick PA layer, a 15 μm thick LLDPE layer, and a 40 μm thick polyethylene blend layer.
[0214] [Example 3] A mixture of 80% by mass of bHDPE (SGF4950) and 20% by mass of acid-modified polyethylene (BYNEL 40E 1053), bPA (Amilan CM2001L), LLDPE (SP0511), LLDPE (UZ3520L), and a mixture of 30% by mass of LDPE (B128) and 70% by mass of LLDPE (UZ2021L) were co-extruded by inflation method. In this way, a laminate with a total thickness of 75 μm was obtained, which includes a 15 μm thick HDPE blend layer, a 5 μm thick PA layer, a 15 μm thick LLDPE layer, a 20 μm thick LLDPE layer, and a 20 μm thick polyethylene blend layer.
[0215] [Example 4] A laminate having a total thickness of 75 μm was obtained in the same manner as in Example 3, except that bPA (Amilan CM2001L) was changed to bPA (RILSAN BESN P20 TL).
[0216] [Example 5] A laminate having a total thickness of 75 μm was obtained in the same manner as in Example 3, except that bPA (Amilan CM2001L) was changed to bPA (VESTAMID Terra DS22).
[0217] [Reference example 1] A laminate having a total thickness of 70 μm was obtained in the same manner as in Example 1, except that bPA (Amilan CM2001L) was changed to PA (5033B).
[0218] [Reference example 2] A laminate having a total thickness of 75 μm was obtained in the same manner as in Example 3, except that bHDPE (SGF4950) was changed to HDPE (HZ5000SF) and bPA (Amilan CM2001L) was changed to PA (5033B).
[0219] [Making packaging bags] Using the laminates obtained in the examples and comparative examples and a high-speed three-sided seal automatic bag making machine (BH-60D, manufactured by Totani Giken Kogyo Co., Ltd.), the temperature was 160°C, the compression time was 0.8 seconds, and the pressure was 3 kgf / cm 2 The mixture was heat sealed under the above conditions to prepare a three-sided pouch.
[0220] [Physical property evaluation] The methods for evaluating the physical properties of the laminate and film are described below. Unless otherwise specified, the environment during measurement of each physical property was a temperature of 23° C. and a humidity of 50% RH. Measurements were performed on three test pieces for each physical property, and the arithmetic mean value of the three values obtained was recorded as the value of each physical property.
[0221] In the following description, the film corresponding to the release layer obtained by peeling the first resin layer (release layer) from the second resin layer (sealant layer) in the laminate is referred to as a release film, and the film corresponding to the sealant layer is referred to as a sealant film.
[0222] <Monomaterial ratio> The content ratio (monomaterial ratio, mass %) of the resin material with the largest content was calculated for the laminate, release film, and sealant film.
[0223] <Peel strength> The laminate was cut to obtain a test piece having a width of 15 mm and a length of 100 mm. Using the test piece and a benchtop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) as a measuring instrument, the peel strength (N / 15 mm width) between the peel layer and the sealant layer in the laminate was measured under the conditions of an initial chuck distance of 100 mm, a peel angle of 180 degrees, and a test speed of 50 mm / min.
[0224] <Appearance (floating between layers)> During each process of laminate manufacturing, the gap between the release layer and the sealant layer (air bubbles and white area of 1 cm2) 2 The above-mentioned points were visually inspected. A laminate in which lifting occurred was rated as ×, and a laminate in which lifting did not occur was rated as ◯.
[0225] <Puncture strength> The puncture strength of the laminate, the release film, and the sealant film was measured according to JIS Z1707:2019. The laminate, the release film, and the sealant film were each cut to obtain a test piece having a width of 5 cm and a length of 5 cm. A tabletop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) was used as a measuring instrument. A semicircular needle having a diameter of 1.0 mm and a tip shape radius of 0.5 mm was pierced into the test piece at a test speed of 50 mm / min, and the maximum strength (N) until the needle penetrated the test piece was measured. In the case of the laminate, the needle was pierced into the sealant layer surface and the release layer surface, and the puncture strength (N) of each was measured. In the case of the release film, the needle was pierced into the surface opposite to the release surface, and the puncture strength (N) was measured. In the case of the sealant film, the needle was pierced into the release surface, and the puncture strength (N) was measured.
[0226] <Seal strength> The laminate was cut to obtain a test piece having a width of 15 mm and a length of 100 mm. Two test pieces were overlapped so that the sealant layers were in contact with each other, and the temperature was 140°C (one-sided heating), the compression time was 1 second, and the pressure was 1 kgf / cm. 2A 15 mm x 15 mm portion of one end of the test piece was heat-sealed under the conditions above to form a sealed portion, and a test specimen was obtained. Except for the test conditions being changed as follows, the seal strength (N / 15 mm width) was measured in accordance with JIS Z1707:2019 using a tabletop tensile compression tester MCT-1150 (manufactured by AND Co., Ltd.) as a measuring instrument under the conditions of chuck distance: 100 mm, peeling mode: T-type peeling, and test speed: 300 mm / min. Specifically, the test specimen was opened 180 degrees so that the sealed portion of the test specimen was in the center of the two grips of the test machine, and both ends of the test specimen were attached to the two grips of the test machine, respectively, and pulled at a speed of 300 mm / min until the sealed portion broke, to obtain the maximum strength (N). The maximum strength (N) measured for the 15 mm wide test specimen was taken as the heat seal strength (N / 15 mm width).
[0227] [Table 1] [Explanation of symbols]
[0228] 1 ...Laminate 10...First resin layer 12...Polyolefin layer 14...Heteroatom-containing resin layer 16...adhesive layer 20...Second resin layer 22...Density is 0.909g / cm 3 Polyethylene layer below 23. Middle class 24…Thermofusible resin layer 25…Extruded resin layer 40...Goods 50...Packaging bag 50a…Storage section 51…Upper 51a…Upper seal part 52…Lower 52a…Lower seal part 53…Side 53a...Side seal part 54…Surface sheet 55…Back sheet 60...Half cut wire
Claims
1. A laminate comprising at least a first resin layer and a second resin layer, the first resin layer is provided so as to be peelable from the second resin layer, the second resin layer is a sealant layer containing polyolefin as a main component, At least one resin layer selected from the first resin layer and the second resin layer contains at least a biomass-derived resin material; Laminate.
2. The laminate according to claim 1 , wherein the first resin layer comprises at least a heteroatom-containing resin layer containing a heteroatom-containing resin as a main component, and the heteroatom-containing resin layer is in contact with the second resin layer.
3. The laminate according to claim 2 , wherein at least a portion of the heteroatom-containing resin is a biomass-derived resin material.
4. The laminate according to claim 3, wherein the heteroatom-containing resin comprises at least one selected from polyamide, ethylene-vinyl alcohol copolymer, polyester, and polyvinyl alcohol.
5. The laminate according to claim 2 , wherein the first resin layer further comprises a polyolefin layer containing a polyolefin as a main component.
6. The laminate according to claim 5 , wherein at least a part of the polyolefin is a biomass-derived resin material.
7. The laminate of claim 5 , wherein the polyolefin layer further contains a modified polyolefin in addition to the polyolefin.
8. The laminate according to claim 1 , wherein the second resin layer comprises a heat-sealable resin layer containing polyolefin as a main component as one surface layer of the laminate.
9. The laminate according to claim 8 , wherein the heat-sealable resin layer contains, as a main component, at least one type of polyethylene selected from linear low-density polyethylene and low-density polyethylene.
10. The second resin layer has a density of 0.909 g / cm 3 3. The laminate according to claim 2, comprising: a polyethylene layer; and a heat-sealable resin layer containing polyethylene as a main component as one surface layer of the laminate, wherein the polyethylene layer in the second resin layer is in contact with the heteroatom-containing resin layer in the first resin layer.
11. The second resin layer has a density of 0.909 g / cm 3 The laminate according to claim 10, further comprising an intermediate layer containing linear low density polyethylene as a main component between the polyethylene layer and the heat-sealable resin layer.
12. The laminate according to claim 1 , having a biomass content of 3% or more.
13. The laminate according to claim 1 , wherein the first resin layer has a biomass content of 10% or more.
14. 2. The laminate according to claim 1, wherein a peel strength between the first resin layer and the second resin layer, measured under conditions of a peel angle of 180 degrees and a test speed of 50 mm / min, is 1.0 N / 15 mm width or less.
15. The laminate of claim 1 which is a coextruded multilayer film.
16. A packaging bag comprising the laminate according to any one of claims 1 to 15.
17. The packaging bag according to claim 16 , further comprising a seal portion formed by fusing the second resin layers in the laminate together.
Citation Information
Patent Citations
Double bag
JP2012126437A